TINDAK PIDANA TANPA KORBAN DI INDONESIA PENGATURAN DAN PROBLEMATIKANYA - Duwi Handoko (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The term of victimless crime in positive criminal law in Indonesia is contained in only one law, namelyLaw Number 11 Year 2012 on the Criminal Justice System of the Child. Although in the law, the term